The Branding Effect of Environmental, Social, and Governance: Market-Based Brand Equity Among Publicly Listed Companies in the Philippines - Doblas, Mark P.; Lagaras , Maria Cecilia P.; Regadio, Faith P.; Panerio, Genevieve G.; Pendang, Tressa Maye S.; Teano, Berlyn M. (International Review of Management and Marketing, 2026)
This paper explores the association between the level of Environmental, Social, and Governance (ESG) performance and market-based brand equity of publicly traded firms. Adopting Signaling Theory, Stakeholder Theory, and Resource-Based View, market-based brand equity is captured using Tobin’s Q measure, while the level of ESG performance is evaluated based on aggregate ESG performance and its disaggregate environmental, social, and governance components. This research uses the balanced panel data of 306 firm-year observations from 51 publicly traded firms in the Philippines in 2018-2023. Two-way fixed effects estimations along with Driscoll-Kraay robustness checks and alternate valuation measures are utilized in this empirical analysis. The results show that the aggregate ESG performance does not have an impact on the market-based brand equity. Nevertheless, the disaggregated analyses indicate that the social component positively influences the level of market-based brand equity irrespective of model specifications, whereas the governance dimension positively affects the market-based brand equity under the logarithmic valuation specification. On the other hand, the environmental component is shown to be insignificant in relation to the market valuation. The paper concludes that investors do not compensate sustainability equally and pay more attention to ESG dimensions that increase the quality of stakeholder relations, corporate legitimacy, and governance. The contribution of the paper to the literature on sustainability and corporate finance is the understanding that the value relevance of ESG is associated with certain sustainability dimensions, and not with ESG performance itself.